Students’ use of power in Foreign Language classroom interaction - Niño, Patricia Kim Jiménez (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper reports the findings of a study which targeted to explore the way as undergraduate students express and use power in classrooms. It also aimed at finding out the sources of students’ power and their viewpoints about the issue. The population was two groups of prospective English teachers from the Modern Languages Program, at Universidad Pedagógica y Tecnológica de Colombia. Direct classroom observation, a teacher’s journal, and semi-structured interviews were the main sources for gathering information. The findings were grouped into four categories dealing with leadership, sources of students’ power, the ideal type of power in classrooms, and some wrong assumptions about power.